Assessing indicators for targeting the needy under the Improved Maternity and Lactating Mother Allowance Program in rural and urban Bangladesh - Ahmed, Akhter; Quabili, Wahid; Tauseef, Salauddin; Ghostlaw, Julie (International Food Policy Research Institute, 2018)
Child stunting in Bangladesh declined dramatically over the past two decades, but remains high at approximately 36 percent (NIPORT 2016). Inadequate maternal nutrition during pregnancy remains prevalent in Bangladesh and is associated with children being born small-for-gestational-age, which is responsible for up to 20 percent of stunting in children between the ages of 1 to 5 years old (Nguyen et al. 2017; Christian et al. 2013). Diets of young children in Bangladesh are also grossly inadequate, further contributing to chronic undernutrition. Renewed efforts to reduce the problem of child undernutrition must focus on improving maternal nutrition (during pregnancy) and the nutrition of the child.